A SUPRACRETACEOUS RADIOLITE FROM MORELOS MEXICO - MULLERRIED, FEDERICO KG (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1950)
A pelecypod, Durania cornu-pastoris, never before recorded from the western hemisphere, is recorded and descr from Los Homos, Morelos Its age is within the upper Turonian or lower Senonian
REV SOC MEX HIST NAT
Keywords: SUPRACRETACEOUS RADIOLITE, MORELOS MEXICO; CIENCIAS DE LA VIDA; PALEONTOLOGIA